Long‐term dynamics and drivers of coral and macroalgal cover on inshore reefs of the Great Barrier Reef Marine Park. Issue 1 (21st October 2019) - Ceccarelli, Daniela M.; Evans, Richard D.; Logan, Murray; Mantel, Philippa; Puotinen, Marji; Petus, Caroline; Russ, Garry R.; Williamson, David H.
Abstract: Quantifying the role of biophysical and anthropogenic drivers of coral reef ecosystem processes can inform management strategies that aim to maintain or restore ecosystem structure and productivity. However, few studies have examined the combined effects of multiple drivers, partitioned their impacts, or established threshold values that may trigger shifts in benthic cover. Inshore fringing reefs of the Great Barrier Reef Marine Park (GBRMP) occur in high‐sediment, high‐nutrient environments and are under increasing pressure from multiple acute and chronic stressors. Despite world‐leading management, including networks of no‐take marine reserves, relative declines in hard coral cover of 40–50% have occurred in recent years, with localized but persistent shifts from coral to macroalgal dominance on some reefs. Here we use boosted regression tree analyses to test the relative importance of multiple biophysical drivers on coral and macroalgal cover using a long‐term (12–18 yr) data set collected from reefs at four island groups. Coral and macroalgal cover were negatively correlated at all island groups, and particularly when macroalgal cover was above 20%. Although reefs at each island group had different disturbance‐and‐recovery histories, degree heating weeks (DHW) and routine wave exposure consistently emerged as common drivers of coral and macroalgal cover. In addition, different combinations of sea‐surface temperature, nutrient and turbidity parameters, exposure to high turbidity (primary) floodwater, depth, grazing fish density, farming damselfish density, and management zoning variously contributed to changes in coral and macroalgal cover at each island group. Clear threshold values were apparent for multiple drivers including wave exposure, depth, and degree heating weeks for coral cover, and depth, degree heating weeks, chlorophyll a, and cyclone exposure for macroalgal cover, however, all threshold values were variable among island groups. Our findings demonstrate that inshore coral reef communities are typically structured by broadscale climatic perturbations, superimposed upon unique sets of local‐scale drivers. Although rapidly escalating climate change impacts are the largest threat to coral reefs of the GBRMP and globally, our findings suggest that proactive management actions that effectively reduce chronic stressors at local scales should contribute to improved reef resistance and recovery potential following acute climatic disturbances.